Study of microstructure, maceral and mineral matter in two different coals of the Nepal Himalaya (Journal of Nepal Geological Society, 2018)
The Eocene coals from the western (Tosh coalfield) and central regions (Jhadewa coalfield) of the Nepal Himalaya have been studied under the petrological and the Scanning Electron Microscopes to explain the mode of occurrence of mineral matter and their microstructural relations with organic constituents. As shown by the results of the coal samples, three kinds of coals in diminishing abundance are moderately dull coal, moderately bright coal and bright coal. Distribution of mineral matter in the Eocene coals shows that the bright coal is rare in western Nepal and the moderately bright coal is abundant in central Nepal. Mineral matter in moderately dull coals contains superficial impregnating and cavity filling. Mineral matter in bright coals contains superficial mounting and pore fillings, but in moderately bright coals contains superficial impregnating, cavity filling, and intimate intergrowth. Mineral matters inmoderately dull coals, moderately bright coals and bright coals respectively range from 38.27 to 47.12 vol%, 12.31 and 15.73 vol%, and 12.31 and 15.73 vol%. The Jhadewa coalfield (central Nepal) contains more macerels than the Tosh coalfield (western Nepal), whereas the Tosh coalfield contains more mineral matter than the Jhadewa coalfield. The results indicate two different origins for coal deposits from two different regions.